(untitled) (Sociologisk Forskning, 1995)
The power of sociology - the sociology of power In this article the relations in which sociological knowledge is produced, read and used, is discussed in a power perspective. Own experiences of sociological production of knowledge is linked to the metatheoretical critique of Pierre Bourdieu and Dorothy E. Smith. Similarities and differences regarding their critique as well as their recommended alternative approaches, are illustrated and discussed. It is argued that a sociological problematization - including a gender perspective - of the position of the researcher in the academic field and the tools that go along with this very position, has to be the basis for the development of a sociology that wants to be an alternative to ”the view from above”, i.e from those in power. Finally, the question of the links from relations of production of sociological knowledge to the ”sociological personality” is raised. Does the ruling perspective dominating the sociological traditions attract ”ruler personalities”? Does is make us all to ”small rulers” ? And does this in its turn result in a strengthening of the ruling perspective within sociology?